Humanistic data art visualization for analyzing learner growth in Challenge Based Learning programs - Tangredi, Domenico; Katics, Giselle; Perna, Stefano (Frontiers in Psychology, 2024)
This perspective article investigates the potential of applying artistic or "humanistic" data visualization to improve the understanding of learner's growth in the context of highly dynamic, learner-centric and experiential educational programs. The article explores the possibility of leveraging a more humanistic or aesthetically driven approach to visual learning analytics in the context of programs using Challenge Based Learning (CBL) as a learning framework. CBL is a relatively new and rapidly expanding educational framework grounded on a rich tradition of constructivist, progressive and experiential learning theories.To illustrate the concept, the authors created two data visualizations, designed to offer a comprehensive overview of learners' growing perceptions. The artistic infographic also provides program managers' insights into class dynamics and the programs' overall impact, enhancing the understanding and effectiveness of student-centered learning journeys. Some suggestions for future research are offered.